Semantic Shifts of the Term Ameen: From Islamic Theology and Qur’anic Exegesis to Electoral Political Discourse - Nirwana AN, Andri; Masbur; Juwaini; Ridwan, Muhammad K.; Elmanaya, Nourelhuda (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
This study examines the term 'Ameen' in the Qur'an and its relevance in the context of the 2024 Presidential and Vice Presidential Elections in Indonesia, where there are symptoms of politicization of religious symbols in the public sphere. The word 'Amen', which is traditionally interpreted as an affirmation of prayer in the worship practice of Muslims, has expanded its meaning  from a spiritual function to a political symbol used as an acronym for a certain pair of candidates. This study employs a qualitative approach using critical discourse analysis with the method of critical discourse analysis to explore the theological meaning and symbolic transformation of the term 'Amen'. Data was obtained through the study of classical and contemporary interpretations, hadiths, campaign documentation, and digital narratives on social media. The results of the study show that the use of 'Amen' in politics tends to reduce the sacred meaning to rhetoric, creating ambiguity between religious expression and political support. This phenomenon has a social impact in the form of polarization, segmentation, and exclusion in Muslim society. By combining symbolic political theory and maqāṣid al-syarī'ah, this study emphasizes the need for a critical awareness of the use of religious symbols in politics so that the sanctity of Islamic texts is not reduced to a pragmatic tool of power.